Organizational safety climate and workplace violence among primary healthcare workers in Malaysia - Sudeash Rajakrishnan; Victor Hoe Chee Wai Abdullah; Nasrin Aghamohammadi (Intelektual Pustaka Media Utama, 2022)
Workplace violence (WPV) has become a global safety and health concern in recent times particularly in the healthcare sector. In addition, low levels of organisational safety climate (OSC) have been associated with higher occurrence of occupational related health outcomes. Hence, the objective of this study was to determine the association between organisational safety climate and workplace violence among government primary healthcare workers. A cross-sectional study among a stratified random sample of 838 primary healthcare workers (HCW) from the nine district health offices under the Selangor state health department. Two standardized self-administered questionnaires were used to obtain data on WPV and OSC. Logistic regression models used to estimate the association between OSC and WPV. Prevalence of WPV was 68.5% whereby verbal abuse was the most common type (65%) followed by bullying (27%), physical violence (6%) and sexual harassment (2%). Nurses (29.7%) were the most affected by WPV. The main perpetrators were relatives of patients (38%). Low level of OSC was also associated with WPV (OR=3.04, 95% CI=1.45-6.41). The results of this study confirmed that safety climate is associated with WPV. Hence, interventions and efforts to prevent WPV among HCW should also include improving organizational safety factors.